2020
DOI: 10.1002/cssc.202001739
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Catalyzed Aqueous N−O Bond Cleavage of 2‐Oxa‐3‐Azabicyclo Compounds to Cyclic cis‐1,4‐Amino Alcohols

Abstract: The N−O bond cleavage of 2‐oxa‐3‐azabicyclo substrates, which are readily prepared by the hetero Diels‐Alder reaction between nitroso dienophiles and cyclic 1,3‐dienes, was effectively catalyzed by heterogeneous copper‐on‐carbon (Cu/C) under aqueous conditions to give the corresponding cyclic cis‐1,4‐amino alcohol derivatives. The present method was applied to the direct incorporation of the hydroxy and amino groups derived from a nitroso substrate into cyclic 1,3‐dienes with cis‐selectivity by the combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Several reductive N-O bond cleavage of isoxazolines and 2-oxa-3-azabicyclic compounds have been studied using copper(0) nanoparticle and heterogeneous copper-on-carbon in the absence of silane. 54,55 It is noteworthy that the reaction without silane gave trace amount of amide, indicating the use of silane is essential (entry 9). To conrm that the reaction was not possible, several control experiments were further performed, which indicated that the copper catalyst was pivotal (entry 12 and 13).…”
mentioning
confidence: 99%
“…Several reductive N-O bond cleavage of isoxazolines and 2-oxa-3-azabicyclic compounds have been studied using copper(0) nanoparticle and heterogeneous copper-on-carbon in the absence of silane. 54,55 It is noteworthy that the reaction without silane gave trace amount of amide, indicating the use of silane is essential (entry 9). To conrm that the reaction was not possible, several control experiments were further performed, which indicated that the copper catalyst was pivotal (entry 12 and 13).…”
mentioning
confidence: 99%